Comparison of Endodontic Treatment Results Yielded from Using Normal Saline with IKI Final Rinse or NaOCl Irrigation: A 30-Month Follow-up Study - Abbaszadegan, Abbas; Nabavizadeh, Mohammadreza; Hoseini Yekani, Ameneh; Khayat, Akbar (Iranian Endodontic Journal, 2013)
Introduction: The aim of this clinical trial was to evaluate and compare the endodontic treatment results of teeth with apical periodontitis after thirty-month recall with two different irrigation regimen: normal saline followed by Iodine Potassium Iodide (IKI) or sodium hypochlorite (NaOCl) irrigation alone. Materials and Methods: Twenty seven patients (30 teeth) who had been included in the first part of our antimicrobial survey were recalled. In previous stage, root canal treatments were performed using either normal saline with IKI final rinse (n=15) or NaOCl (n=15) as irrigating solutions. Bacterial samples were taken before and after instrumentation. In this stage, three patients (6 teeth) were excluded from the follow-up schedule since they did not respond to the recall requests. The remaining 24 subjects (12 teeth in each NaOCl and IKI group) were examined clinically and radiologically. Post-operative and follow-up images were coded, blindly evaluated and given a periapical score according to PAI scoring system. The outcome was assessed in two ways; first, the changes in PAI score from base line to the follow-up evaluation in each group were assessed by wilcoxon signed rank test. In addition, Mann-Whitney U test was used to compare the differences between the post-operative and follow-up images of treatment groups. Second, the dichotomous variables as “healed” or “not healed” were compared. Results: The Median (Min, Max) PAI scores for NaOCl group and IKI group were both 5 (3, 5) for immediate post-operative radiographs and declined to 1 (1, 2) and 2 (1, 2), respectively. A statistically significant decrease in PAI score from the base line to the follow-up evaluation was seen in both groups (P=0.002). The decrease in NaOCl group was higher significantly in comparison to IKI group (P=0.036). One hundred percent of the teeth were healed in both groups (PAI≤2) and no teeth showed any abnormal clinical findings. Conclusion: Root canal irrigation with NaOCl resulted in a significant higher decrease in PAI scores in comparison to irrigation with normal saline followed by IKI final rinse. Although, according to results of 30-months recall, complete bone formation was observed in all samples in both groups and no teeth showed any abnormal clinical findings. These findings depict the weight of all important clinical and biological factors which together impact the results of a successful endodontic treatment.